(untitled) (Research, Society and Development, 2020)
People management has evolved its concepts, methods and techniques over time by providing new organizational approaches to human capital. The article aimed to apply the inferential multivariate statistical technique to the proposed constructor to clarify whether the proposed measurement model is coherent, well-adjusted and relevant among its variables. Confirmation factor analysis (CFA) was used to identify whether the proposed model is consistent and multivariate analysis provided the validity of the correlations between the variables. The administration of the research involved nineteen campuses of the Federal Institute of Education of Mato Grosso that are geographically dispersed. The data collection obtained the return of 60%, composing in this measure a sample with non-probabilistic characteristic, which still favored the operationalization of inferential multivariate statistics. This study successfully tests the empirical relationship between organizational behavior and the principles of meritocracy on the campuses. CFA corroborated with statistical tests the suitability of the structural modeling of the builder. The model was confirmed to be well adjusted (Goodness-of-fit Index = 0.97, Normed Fit Index = 0.99, Incremental Fit Index = 1.00, and Comparative Fit Index = 1.00). The instrument presented a high internal reliability, the multivariate analysis verified that the coefficients of total effect between the variables of meritocracy and organizational behavior (OB) are consistent, and it was also measured that the OB variables proposed in the model are highly correlated.